Acoustic Correlates of English Lexical Stress Produced by Chinese Dialect Speakers Compared to Native English Speakers - Guo, Xingrong (Frontiers in Psychology, 2022)
English second language learners often experience difficulties in producing native-like English lexical stress. It is unknown which acoustic correlates such as fundamental frequency (F0), duration and intensity are the most problematic for Chinese dialect speakers. The present study investigated the prosodic transfer effects of first language (L1) regional dialects on the production of English stress contrasts. Native English speakers (N=20) and Chinese learners (N=60) with different dialect backgrounds (Beijing, Changsha and Guangzhou dialects) produced the same stimulus including both trochaic and iambic patterns. Results showed that (a) all participants produced the stressed syllable with greater values of F0, duration and intensity; (b) Native speakers of English employed an exquisite combination of F0, duration and intensity, while the dialect groups transfer their native prosody into their production of English lexical stress, resulting in the deviation or abnormality of acoustic cues. Results suggest that L1 native dialect background is considered as a potentially influential factor which may transfer in L2 speech encoding and decoding process.